2023
DOI: 10.3389/fpls.2023.1163357
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, evolution and expression pattern analysis of the GATA gene family in Sorghum bicolor

Abstract: The GATA family of transcription factors is zinc finger DNA binding proteins involved in a variety of biological processes, including plant growth and development and response to biotic/abiotic stresses, and thus play an essential role in plant response to environmental changes. However, the GATA gene family of Sorghum (SbGATA) has not been systematically analyzed and reported yet. Herein, we used a variety of bioinformatics methods and quantitative Real-Time Polymerase Chain Reaction (qRT-PCR) to explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Phylogenetic analysis indicated that the GATA proteins from P. ginseng, A. thaliana, and O. sativa were classified into A, B, C, and D groups. This classification is consistent with the grouping of GATA proteins in Setaria italica [64], A. hypogaea L. [66], Populus alba [69], Sorghum bicolor [70], Zea mays L. [71], and Fagopyrum tataricum [72]. Specifically, subgroup A had the highest number of GATAs, and members within the same subgroups exhibited higher sequence similarity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Phylogenetic analysis indicated that the GATA proteins from P. ginseng, A. thaliana, and O. sativa were classified into A, B, C, and D groups. This classification is consistent with the grouping of GATA proteins in Setaria italica [64], A. hypogaea L. [66], Populus alba [69], Sorghum bicolor [70], Zea mays L. [71], and Fagopyrum tataricum [72]. Specifically, subgroup A had the highest number of GATAs, and members within the same subgroups exhibited higher sequence similarity.…”
Section: Discussionsupporting
confidence: 83%
“…The gene structure analysis revealed that introns ranged from 1 to 27, while the exons ranged from 1 to 28. These obtained exons and introns were significantly higher than those observed in GATA proteins in other plants, such as S. italica [64], A. hypogaea L. [66], Populus alba [69], and S. bicolor [70]. This suggests that GATA genes may undergo gain or loss of exons or introns throughout the process of chromosomal rearrangements in different species.…”
Section: Discussionmentioning
confidence: 69%
“…Several candidate transcription factors were identified; the insert coding for a GATA transcription factor 22 protein was identified in both Screen 1 and Screen 2 and was selected for further characterization. The open reading frame (ORF) of the protein, hereafter named SbGATA22 based on NCBI nomenclature (also called SbGATA32 by Yao et al [48]), was found to be fused in-frame to the GAL4 activation domain. The minimal inhibitory concentration of the antibiotic Aureobasidin A (AbA) required for cDNA library screening was determined by growing the bait yeast strains (Y1H pAbAi-Native and Y1H pAbAi-Mutant) on SD/-Ura media with or without the antibiotic.…”
Section: Identification Of a Novel Gata Transcription Factor That Bin...mentioning
confidence: 99%
“…In rice, GATA transcription factors have also been implicated in abiotic stress responses, with gene expression changing in response to salinity, drought, and abscisic acid (a phytohormone with roles in drought and salt stress) [62]. Despite the knowledge of GATA transcription factor function in rice, the extent of functional conservation between monocots has only recently started to be explored and remains largely computational [48]. These computational analyses in other monocot species, such as wheat [63] and foxtail millet [64], also predict roles for GATA transcription factors in response to stress and in hormone signaling pathways.…”
Section: Gata Transcription Factors In Plant Development and Stress R...mentioning
confidence: 99%
See 1 more Smart Citation